The Nucleophilicity of Persistent α‐Monofluoromethide Anions. (15th September 2016) - Zhang, Zhe; Puente, Ángel; Wang, Fang; Rahm, Martin; Mei, Yuncai; Mayr, Herbert; Prakash, G. K. Surya
Abstract: α‐Fluorocarbanions are key intermediates in nucleophilic fluoroalkylation reactions. Although frequently discussed, the origin of the fluorine effect on the reactivity of α‐fluorinated CH acids has remained largely unexplored. We have now investigated the kinetics of a series of reactions of α‐substituted carbanions with reference electrophiles to elucidate the effects of α‐F, α‐Cl, and α‐OMe substituents on the nucleophilic reactivities of carbanions.